PENGARUH MEDIA GAMBAR SERI MODIFIKASI TERHADAP KEMAMPUAN BERCERITA ANAK DI TAMAN KANAK-KANAK AL HIDAYAH TABING KOTA PADANG - Isra Nova; Yulsyofriend; Serli Marlina; Saridewi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was conducted to analyze the effect of using modified series of pictures on the storytelling ability of 5-6 year old children at Al Hidayah Tabing Kindergarten, Padang City. The study used a quantitative approach with a quasi-experimental method and implemented a Nonequivalent Control Group Design. The research subjects consisted of 20 children in group B, divided into 12 children in the experimental class and 8 children in the control class. Data were collected through structured observations using an instrument in the form of a storytelling ability checklist that included aspects of listening to stories, answering questions, conveying ideas, using appropriate vocabulary, and retelling the story sequentially. Treatment was given through learning activities using modified series of pictures with the theme of butterfly metamorphosis. The results showed an increase in the average storytelling ability in the experimental class, namely from a score of 10.43 in the pre-test to 16.14 in the post-test. Meanwhile, in the control class the average score increased from 8.43 to 10.29. Based on the gain score analysis, the average increase in the experimental class reached 5.57, while the control class was only 1.86. The results of the Independent Sample t-Test showed a significance value of 0.000 (<0.05), so the alternative hypothesis (H₁) was accepted. Thus, it can be concluded that the use of modified series of pictures media has a significant influence in improving the storytelling ability of children aged 5–6 years at Al Hidayah Tabing Kindergarten, Padang City.